The Influence of Student Facilitator Learning Model and Explaining Using Mind Mapping on The Results of Learning Natural Science - Brata Sang Made; I Nyoman Dantes; Ndara T. Renda (Journal of Psychology and Instruction, 2019)
The aim of this research to know about: 1) the effectiveness of implementation of learning SFAE with Mind Mapping for IPS at V grade in Gugus VI Kintamani. 2) The difference of the result in IPA between students who followed learning conventional for V grade Gugus V Kintamani. The type of this research is quasi experiment with non-equivalent posttest only, control group design. The sample in this research is all of the students in V grade SDN langgahan with total 20 students and student in V grade SDN Awan is 22 student from the total students is 109 students. Random sampling technique used to determine experiment class and control. The method of data collection is used statistics descriptive, test-t , and ANAVA –the result shows about: 1) There is the effective influence implementation about SFAE learning with Mind Mapping of the result of learning IPA V grade gugus VI kintamani district with the high effectiveness with result of ES = 2,93 and 2) for the difference to the result of the IPA between students with following learning with using SFAE learning of Mind Mapping and the student followed conventional learning with the significant assessment (28,42>4,08) ,therefore in the conclusion learning of SFAE models with Mind Mapping has the influence for the result of study IPA for student in V Grade in Kintamani district.